Colour implementation with Fauvism Style to Limited Amination Character “We Are Different Yet We Are Same” - Nur Hasanah Firdaus (Universitas Multimedia Nusantara, 2018)
Fauvism is an art form in the beginning of modernism art era with focusing on color implementation that doesn’t have to represent the reality, showing the strong bond of the artist with the atmosphere he drew. Fauvism color implementation will be implemented to the short animation film with limited animation technique, “We Are Different, yet We Are The Same”. In the making, the writer uses qualitative research method. Data that gathered used as a base for the writer on character designing in limited animation “We Are Different, yet We Are The Same” with fauvism style